2004
DOI: 10.1002/bit.20250
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of equiaxial and uniaxial strain on mesenchymal stem cells

Abstract: Bone marrow mesenchymal stem cells (MSCs) can differentiate into a variety of cell types, including vascular smooth muscle cells (SMCs), and have tremendous potential as a cell source for cardiovascular regeneration. We postulate that specific vascular environmental factors will promote MSC differentiation into SMCs. However, the effects of the vascular mechanical environment on MSCs have not been characterized. Here we show that mechanical strain regulated the expression of SMC markers in MSCs. Cyclic equiaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
305
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(331 citation statements)
references
References 39 publications
(40 reference statements)
21
305
1
4
Order By: Relevance
“…Previous work has shown that mechanical strain has an effect on proliferation and differentiation of vascular SMCs, including up-regulation of various SMC contractile markers (8)(9)(10), and the cells aligned perpendicularly to the axis of strain (11). Similarly, we have shown that when MSCs are subjected to conditions of cyclic uniaxial strain on silicone membranes, the cells show an initial up-regulation of SMC markers that eventually drops back to basal levels after the cells align perpendicularly to the axis of strain as a means of reducing the effective stress on their cytoskeleton (12). This cellular orientation differs from in vivo conditions where vascular SMCs align in the circumferential direction (13,14) or, in some cases, in a helical pattern (15) in the arterial wall and SMCs are subject to circumferential cyclic strain because of the pulsatile nature of the blood pressure.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Previous work has shown that mechanical strain has an effect on proliferation and differentiation of vascular SMCs, including up-regulation of various SMC contractile markers (8)(9)(10), and the cells aligned perpendicularly to the axis of strain (11). Similarly, we have shown that when MSCs are subjected to conditions of cyclic uniaxial strain on silicone membranes, the cells show an initial up-regulation of SMC markers that eventually drops back to basal levels after the cells align perpendicularly to the axis of strain as a means of reducing the effective stress on their cytoskeleton (12). This cellular orientation differs from in vivo conditions where vascular SMCs align in the circumferential direction (13,14) or, in some cases, in a helical pattern (15) in the arterial wall and SMCs are subject to circumferential cyclic strain because of the pulsatile nature of the blood pressure.…”
supporting
confidence: 52%
“…Several studies have shown that SMC response to this stimulus involves up-regulation of smooth muscle markers such as h-caldesmon (8), SM-1͞2 (24), and SM ␣-actin (9). However, our previous study revealed a decrease in the smooth muscle markers SM ␣-actin and SM22 when MSCs were stimulated with cyclic equiaxial strain (12).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…O'Cearbhaill et al [29] did not observe vWF expression on the protein level under static or mechanically stimulated conditions, nor did they observe a significant change in vWF at the mRNA level. The combined effect of radial stress and hoop stress used in the experiment may have surpassed the effect of shear stress in cell differentiation, because cyclic stress promotes the expression of smooth muscle-like properties [10,30,31] . Because MSCs can also differentiate along SMC lines, we hypothesized that differentiation along the endothelial line might accompany shear stress-induced negative regula- tion of the expression of SMC-related markers, such as SM α-actin and calponin.…”
Section: Discussionmentioning
confidence: 99%
“…Uniaxial stretching transiently enhances the expression of smooth muscle markers like smooth muscle a-actin in human BMSCs, whereas equilateral stretching inhibits smooth muscle differentiation. 111 …”
Section: Mechanical Forcesmentioning
confidence: 99%